Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage Dan Kepemilikan Saham Publik Pada Pengungkapan Corporate Social Responsibility - Andriana, I Komang Gede Surya; Wahyu Purna Anggara, I Wayan Gde (E-Jurnal Akuntansi, 2019)
Corporate Social Responsibility is a strategy that is applied by a company as evidence of the company's social responsibility to the environment and social companies so that the company can grow sustainably. This study aims to determine the effect of company size, profitability, leverage and public share ownership on CSR disclosures of food and beverage companies. Measurement of index of social responsibility disclosure with Global Reporting Initiative Generation 4.This research was conducted on food and beverage companies listed on the Indonesia Stock Exchange in the 2014-2016 period. Samples were selected using purposive sampling and obtained 33 data that met the sample criteria. The research data was analyzed using multiple linear regression methods. The results showed that firm size and profitability had a positive effect on Corporate Social Responsibility disclosure, while Leverage and public share ownership had no effect on the disclosure of Corporate Social Responsibility. Keywords : Corporate Social Responsibility; company size; profitability; leverage; public share ownership.